Al-Quran Dan Mukjizat Angka - Samsul Ariyadi (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2024)
The word miracle in the Indonesian dictionary is defined as "a miraculous event that is difficult for the human mind to reach." This meaning is not the same as the meaning of the word in terms of the Islamic religion. In language, the origin of the word miracle or معجزة is عجز which consists of three letters, namely Ain, Jiem and Zay. According to Ibn Faris the word has two meanings. The first is from the word Ajaza or عجز with wazan fa'ala which means al-Dlo'fu or weak, the second meaning is from something. The opposite of the word ajaza which means weak is alhazm or الحزم which means strength of heart. Therefore, the meaning of ajaza can be interpreted as a weakness in the form of inability that is abstract or non-physical in nature, although it does not preclude the meaning of weakness which means physical incapacity. While the second meaning is Ajuza with scales (read: wazan) Fa'ula which means the end of a case